2013
DOI: 10.3855/jidc.4102
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B seroprevalence in children and women and the impact of the hepatitis B vaccination program in the Black Sea Region of Turkey

Abstract: Introduction: This study aimed to determine the seroprevalence of hepatitis B virus (HBV) infection in children and females in the middle Black Sea Region of Turkey and to assess the impact of the universal infant hepatitis B vaccination program started in 1998. Methodology: The laboratory records of 12,057 patients who attended the Samsun Maternity and Children's Hospital between January 2007 and November 2009 were evaluated retrospectively. In this period, hepatitis B surface antigen (HBsAg), the antibody to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…infection with HBV, an acute and chronic communicable disease, has developed into a major global health problem (7,8,25). at present, vaccination is regarded as the most effective prevention measure against HBV infection; however, ~5-10% of healthy immunocompetent subjects are non-responsive (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection with HBV, an acute and chronic communicable disease, has developed into a major global health problem (7,8,25). at present, vaccination is regarded as the most effective prevention measure against HBV infection; however, ~5-10% of healthy immunocompetent subjects are non-responsive (26).…”
Section: Discussionmentioning
confidence: 99%
“…at present, vaccination is regarded as the most effective prevention measure against HBV infection; however, ~5-10% of healthy immunocompetent subjects are non-responsive (26). Previous studies demonstrated that the male gender was associated with increased incidence of non-response to HBV vaccination (19,25,27), whereas others indicated that there was no sex-based difference in the immune response to the HBV vaccine between males and females (28,29). To clarify the biological influences of sex on the immune response to the HBV vaccine, the present study aimed to investigate the sexual dimorphism in the immune response to HBV vaccination in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 20 studies assessed 31,770 children for HBsAg prevalence in the E and M countries and were considered in the meta-analysis. Of these, 3 studies were conducted in Iran (13,44,45), 5 studies in Pakistan (11,(46)(47)(48)(49), 4 studies in Turkey (10,(50)(51)(52), and 2 in Yemen (53,54). Single studies were performed in the following nations: Afghanistan (55), Cyprus (12), Egypt (56), Iraq (57), Lebanon (58), and Palestine (8).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies published between 2013-2022 have shown HBsAg positivity rates of 3.5%, 1.1%, and 0.3% among people born in 1998 and after in Turkey, respectively ( 3 , 12 , 13 ). Although it has been nearly three decades since the HBV vaccine was included in the national vaccine program, the number of comprehensive studies related to seroprevalence in the population, including adults and the pediatric population, is low in our country.…”
Section: Introductionmentioning
confidence: 99%